ANTIOXIDANT PROTECTION OF WHITE DRY WINE - R, Irgasheva G. (Journal of Higher Education and Academic Advancement, 2024)
General Background: The oxidative enzymatic processes in wine production significantly influence the quality and stability of white dry wines, affecting their sensory attributes and shelf life. Specific Background: Various technological methods utilized in winemaking can alter the intensity of these oxidative processes, subsequently leading to secondary oxidation-reduction reactions that impact the final product. Understanding the chemistry of enzyme preparations is crucial for optimizing wine production technologies based on the specific types of enzymes used. Knowledge Gap: Despite the acknowledged importance of enzyme activity in wine production, there is a lack of comprehensive research addressing how different enzymatic preparations can be effectively employed to manage oxidative processes during winemaking. Aims: This study aims to elucidate the role of antioxidant protection in white dry wines, focusing on how various technological methods and enzyme preparations influence oxidative enzymatic activities. Results: The findings indicate that specific enzymatic treatments can significantly reduce oxidative stress in white dry wines, enhancing their antioxidant capacity and improving overall wine quality. Comparative analyses revealed notable differences in oxidative stability based on the enzyme types and technological approaches employed. Novelty: This research contributes novel insights into the interplay between enzymatic preparations and oxidative processes in winemaking, highlighting practical applications for improving wine production technologies. Implications: The implications of this study underscore the importance of tailoring winemaking techniques to incorporate appropriate enzyme preparations, thereby optimizing the antioxidant protection of white dry wines. Such advancements can lead to higher quality products with improved sensory characteristics and prolonged shelf life, benefiting both producers and consumers in the wine industry.